2019
DOI: 10.1111/jcmm.14205
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PAI‐1 limits chemotherapy resistance in lung cancer through suppressing myofibroblast characteristics of cancer‐associated fibroblasts

Abstract: Plasminogen activator inhibitor‐1 (PAI‐1) promotes pulmonary fibrosis through increasing myofibroblast (MF) characteristics, expressing alpha‐smooth muscle actin (α‐SMA) in fibroblasts. Fibroblasts in the tumour stroma are called cancer‐associated fibroblasts (CAFs). Some CAFs have MF characteristics and substantially promote tumour progression and chemotherapy resistance. This study determined whether inhibition of PAI‐1 suppressed MF characteristics of CAFs and limited chemotherapy resistance in lung cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 32 publications
2
36
0
Order By: Relevance
“…Masuda et al showed that stromal cells express higher levels of PAI-1 than cancer cells in lung adenocarcinoma tissues and that PAI-1 expression correlated with αSMA levels and depth of tumor invasion [43]. These findings are consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Masuda et al showed that stromal cells express higher levels of PAI-1 than cancer cells in lung adenocarcinoma tissues and that PAI-1 expression correlated with αSMA levels and depth of tumor invasion [43]. These findings are consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Suppressing alpha-smooth muscle actin (α-SMA) myofibroblastic CAFs—which share the phenotypic traits of fibroblasts and smooth muscle cells, secrete ECM, and generate mechanical tension within tissue through cell contraction [ 46 ]—through the inhibition of plasminogen activator inhibitor-1 (PAI-1) limits resistance to cisplatin in lung cancer [ 47 ]. CAFs in tissue sections from lung carcinomas incubated with or without cisplatin turned out to be much less sensitive to cisplatin when compared to isolated CAFs, indicating that the TME also attenuates the sensitivity of lung cancer CAFs to cisplatin [ 48 ].…”
Section: Lung Cancermentioning
confidence: 99%
“…These FAP-specific T cells recognize and destroy FAP+CAFs with subsequent antitumor effects ( 113 ). Some CAFs possess myofibroblast characteristics and express α-SMA, which can significantly promote NSCLC resistance to chemotherapy via the expression of high levels of inflammatory cytokines and chemokines ( 114 ). Plasminogen activator inhibitor-1 (PAI-1) can promote the MF characteristics of CAFs, and the expression of PAI-1 in CAFs is correlated with the expression of α-SMA ( 114 ).…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Some CAFs possess myofibroblast characteristics and express α-SMA, which can significantly promote NSCLC resistance to chemotherapy via the expression of high levels of inflammatory cytokines and chemokines ( 114 ). Plasminogen activator inhibitor-1 (PAI-1) can promote the MF characteristics of CAFs, and the expression of PAI-1 in CAFs is correlated with the expression of α-SMA ( 114 ). PAI-1 inhibitors also decrease the expression levels of α-SMA and inhibit the MF characteristics of CAFs, improving chemotherapeutic efficacy in NSCLC ( 114 ).…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
See 1 more Smart Citation